Phosphine Oxide Indenoquinoline Derivatives: Synthesis and Biological Evaluation as Topoisomerase I Inhibitors and Antiproliferative Agents - Alba Rodriguez-Paniagua; Cinzia Tesauro; Birgitta R. Knudsen; Maria Fuertes; Concepción Alonso (Molecules, 2024)
The synthesis of phosphorous indenoquinolines and their biological evaluation as topoisomerase 1 (TOP1) inhibitors and antiproliferative agents were performed. First, the preparation of new hybrid 5H-indeno[2,1-c]quinolines with a phosphine oxide group was performed by a two-step Povarov-type [4+2]-cycloaddition reaction between the corresponding phosphorated aldimines with indene in the presence of BF3·Et2O. Subsequent oxidation of the methylene present in the structure resulted in the corresponding indeno[2,1-c]quinolin-7-one phosphine oxides 10. The synthesized derivatives were evaluated as TOP1 inhibitors showing higher inhibition values than CPT at prolonged incubation times (5 min). Inhibition of TOP1 was even observed after 30 min of incubation. The cytotoxic activities of these compounds were also studied against different cancer cell lines and a non-cancerous cell line. While some compounds showed cytotoxicity against some cancerous cells, none of the compounds showed any cytotoxicity against the non-cancerous cell line, MRC-5, in contrast to CPT, which exhibits high toxicity against this cell line. These results represent a very interesting advance since the heterocyclic phosphine oxide derivatives have important properties as TOP1 inhibitors and show an interesting cytotoxicity against different cell lines.